Inovasi Hidroganik dan Minapadi: Kajian Ekonomi dan Efisiensi Lahan - FAHDYNIA KARNIRA GUNAWAN; Akhmad Adi Sulianto; Fitri Candra Wardana; Damanhuri Damanhuri (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2024)
Agricultural efficiency and sustainability are major challenges amidst limited land availability and increasing food demand. Pusat Pelatihan Pertanian dan Pedesaan Swadaya (P4S) Bengkel Mimpi in Malang Regency integrates the agriculture and fisheries sectors through two methods: hydroganic and mina padi systems. This study aims to analyze the economic feasibility and land efficiency of the two systems applied for rice and catfish cultivation at P4S Bengkel Mimpi. Using quantitative descriptive method, the analysis was conducted using cost and income approach, NPV, DPP, B/C Ratio, BEP, and IRR. The results of the analysis on 100 m2 of land show that the hydroganic system has an NPV of IDR 57,655,541.40, a DPP of 13.65 months, a B/C of 3.95, and an IRR of 20%, with an increase in land productivity of up to 580%. Meanwhile, the mina padi system has an NPV of IDR 3,706,655.25, DPP of 5.67 months, B/C of 3.05, and IRR of 58%, with a faster return on investment. These findings suggest that hydroganic system is superior in land productivity, while the mina padi offers a shorter return on investment, providing strategic recommendations for the application of agricultural and aquaculture integration technologies.